2014
DOI: 10.1186/s13054-014-0559-0
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital induction of mild hypothermia with cold normal saline for cardiac arrest: more harm than good?

Abstract: No abstract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our previous study demonstrated that intravenous infusion of cold saline (ICS) was not the correct choice as an intra-arrest cooling method [ 8 ]. ICS is not an ideal method to maintain target temperature and an excessive volume load may compromise the resuscitation outcomes [ 9 , 10 ]. However, ICS is an attractive strategy to achieve early cooling after resuscitation when compared with surface cooling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that intravenous infusion of cold saline (ICS) was not the correct choice as an intra-arrest cooling method [ 8 ]. ICS is not an ideal method to maintain target temperature and an excessive volume load may compromise the resuscitation outcomes [ 9 , 10 ]. However, ICS is an attractive strategy to achieve early cooling after resuscitation when compared with surface cooling.…”
Section: Introductionmentioning
confidence: 99%
“…However, ICS is an attractive strategy to achieve early cooling after resuscitation when compared with surface cooling. ICS is easy to administrate and has a shorter induction period [ 3 , 9 , 11 ]. Therefore, in-time limited volume ICS combined with surface cooling might be a better cooling strategy following resuscitation.…”
Section: Introductionmentioning
confidence: 99%